2017
DOI: 10.1103/physreva.96.022312
|View full text |Cite
|
Sign up to set email alerts
|

Optimal discrimination of single-qubit mixed states

Abstract: We consider the problem of minimum-error quantum state discrimination for single-qubit mixed states. We present a method which uses the Helstrom conditions constructively and analytically; this algebraic approach is complementary to existing geometric methods, and solves the problem for any number of arbitrary signal states with arbitrary prior probabilities. It has long been known that the minimum error probability is given by the trace of the Lagrange operator, Γ. The remarkable feature of our approach is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…For δ = 0 our results agree with previous work [19,27]. As we have produced an analytic solution, it is also possible to use this to solve problems where state discrimination arises as a smaller part of a problem, as occurs when multiple copies are available [30].…”
Section: Optimal Three-element Povmsupporting
confidence: 87%
See 1 more Smart Citation
“…For δ = 0 our results agree with previous work [19,27]. As we have produced an analytic solution, it is also possible to use this to solve problems where state discrimination arises as a smaller part of a problem, as occurs when multiple copies are available [30].…”
Section: Optimal Three-element Povmsupporting
confidence: 87%
“…By writing Γ −1 in the form 1 2 (a1 + b ·σ), we find three linear equations in three unknowns. As described in [27] and [37], we may assume from symmetry that the optimal POVM will be in the same plane as the states, so b z = 0, and hence find a, b x , b y . Thus we can find Γ and hence P Corr , the optimal probability of correctly identifying the state which was sent, as P Corr = k p k Tr(ρ k π k ) = Tr(Γ) = 4a a 2 −|b| 2 .…”
Section: Optimal Three-element Povmmentioning
confidence: 99%
“…The smoothing parameter p accounts for the amount of coherent evolution given from H with respect to the irreversible evolution given by the Lindblad operators, and it allows to interpolate between a quantum walk (p = 0) and a classical random walk (p = 1). On the other side, quantum state discrimination has been one of the first problems faced in quantum information theory [41][42][43][44][45][46][47][48], but it is still a flourishing research field as demonstrated from recent theoretical [49][50][51][52][53][54] and experimental works [55][56][57][58][59][60], also considered in relation to machine learning approaches [61]. In its most general formulation, an observer wants to guess the quantum state of a system that is prepared in one of a set of feasible states, possibly by optimizing the measurement operators to apply on the system.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to qubit state discrimination, the symmetry operator K determines the possible measurement strategies. Specifically, the following cases exist [8]:…”
Section: Preliminariesmentioning
confidence: 99%